International sport governing bodies as agents of diffusion—The case of World Athletics - Konjer, Mara; Meier, Henk Erik; Krieger, Jörg (Frontiers in Sports and Active Living, 2022)
The current paper conceptualizes international sport governing bodies (ISGBs) as “agents of diffusion,” whose key strategic interest is in the broadest participation in their sports. Our research examines the impact of a specific diffusion strategy, adopted by World Athletics in 2008, which was essentially the decentralization of decision-making power to license athletics events, and which aimed to increase the sports' visibility and accessibility, especially in previously underdeveloped markets like Africa. We evaluate these efforts' impact by analyzing data from the season's bests lists of World Athletics from 2001 to 2019. Therefore, we employ multilevel regressions. The results are complex but instructive. We find that the efforts were of limited success especially in target regions. Still, the strategy inspired more countries to invest in both hosting new events and sending athletes to new disciplines. However, our results cast some doubt about the sustainability of these efforts. The need for a better conceptualization of relevant domestic factors becomes evident. Furthermore, we find that diffusion strategies, which do not offer material incentives, are of limited efficacy.